Mega molluscs! - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
Many Pacific islands, particularly sparsely populated reef areas, have had their natural stocks of giant clam poached to near extinction. The clams are an important part of the reef ecosystem as well as traditionally being an important food source,...